The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1088/1361-6501/ac62c9
|View full text |Cite
|
Sign up to set email alerts
|

An improved snow depth retrieval method with adaptive noise reduction for GPS/GLONASS/Galileo/BDS multi-frequency signals

Abstract: The Global Navigation Satellite System interferometric reflectometry (GNSS-IR) technique is an effective method to monitor snow depth. The detrended signal-to-noise ratio (dSNR) series is analyzed by Lomb–Scargle periodogram (LSP) to extract the characteristic frequency, which can be converted to the snow depth. However, the dSNR data are greatly affected by noise in the observation environment, which leads to the abnormal characteristic frequency and low accuracy of snow depth retrieval. In order to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the field of remote sensing, GNSS-R technology has received increasing attention, and many scientists are continuously researching it. GNSS-R technology has been widely used to monitor sea level height [4][5][6], snow depth [7][8][9], soil moisture [10][11][12], and sea ice detection [13,14], etc. In the field of snow depth retrieval technology, Larson et al [15] used global positioning system (GPS) receivers and traditional methods to monitor heavy snowfall, respectively, and the experimental results showed that the snow depth could be effectively monitored using GPS receivers, and the monitoring results were very similar to the classical methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of remote sensing, GNSS-R technology has received increasing attention, and many scientists are continuously researching it. GNSS-R technology has been widely used to monitor sea level height [4][5][6], snow depth [7][8][9], soil moisture [10][11][12], and sea ice detection [13,14], etc. In the field of snow depth retrieval technology, Larson et al [15] used global positioning system (GPS) receivers and traditional methods to monitor heavy snowfall, respectively, and the experimental results showed that the snow depth could be effectively monitored using GPS receivers, and the monitoring results were very similar to the classical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The Global Navigation Satellite System (GNSS) is satellite-based all-weather navigation, positioning, and timing system [1][2][3]. At present, the leading satellite navigation systems used around the world are the US GPS (Global Positioning System), the Chinese Beidou-3 global satellite navigation system, the Russian GLONASS (Global Navigation Satellite System), and the European Galileo system [4][5][6][7]. With the deterioration of the electromagnetic environment and the escalation of interference complexity, including concepts such as electronic warfare and navigation warfare, which have received a great deal of attention in modern combat systems, anti-jamming has become an essential function of satellite navigation receivers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…BDS-3 comprises satellites in three distinct orbits, namely the medium The BDS-3 multi-frequency signals, coupled with the three kinds of satellites in MEO, IGSO and GEO orbits, are increasing the research dimension in the GNSS community. In both BDS-only and multi-GNSS constellations, a considerable volume of research has followed in different fields such as multipath [2,3], signal-to-noise ratio (SNR) [4], GNSS interferometric reflectometry [5,6], quality of BDS products [7,8], precise time transfer [9,10], and ambiguity resolution (AR) [11]. While multi-frequency and multi-constellation GNSS may be applied in such broad areas, the increase in signals itself complicates the treatment of biases in the formulated observables.…”
Section: Introductionmentioning
confidence: 99%